Digestibility of the cottonseed meal with or without addition of protease and phytase enzymes in swine diet - doi: 10.4025/actascianimsci.v34i3.12360 - Izaura Maria Barros de Lorena-Rezende; Wilson Moreira Dutra Junior; Fabio Monteiro Rezende; Liliane Olimpio Palhares; Maria do Carmo Mouhaupt Marques Ludke; Carlos Boa-Viagem Rabello (Acta Scientiarum. Animal Sciences, 2012)
This study evaluated the digestibility of cottonseed meal with or without addition of enzymes (phytase and protease) for growing pigs. It was used 18 barrows, housed in metabolism cages, distributed in a completely randomized design, standardizing body weight (bw) with average of 25.8 ± 3.6 kg, with three treatments and six repetitions. The treatments consisted of a reference diet based on corn and soybean meal, the second treatment with replacement of 30% of the reference diet by cottonseed meal without enzymes, and the third with 30% of the reference diet replaced by cottonseed meal with added enzymes. Was determined the digestible protein, digestible energy, digestibility of dry matter, energy and protein. It was also registered the balance of nitrogen and phosphorus. The use of cottonseed meal with the addition of enzymes in diets for growing pigs has no effect on the digestibility of dry matter, gross energy and crude protein, but improved the absorption of phosphorus, consequently reducing its excretion in the feces. There was no improvement in nitrogen balance in the diets containing cottonseed meal with enzymes.